2004
DOI: 10.17221/3798-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, phosphorus, potassium fertilizers and manure on growth and productivity of the peach cultivars Springtime and Redhaven

Abstract: The response of the peach cvs. Springtime and Redhaven to nitrogen, phosphorus, potassium fertilizers and manure is reported. The research was conducted during a period of 10 years. The following fertilizer combinations were used: control (no fertilization), N, P, K, NP, NK, PK, PK, manure, N + manure, P + manure, K + manure, NP + manure, NK + manure, <br />PK + manure, NPK + manure. The following measurements were performed: a) productivity (kg/tree); b) mean fruit weight (g); c) fruit number per tree;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
6
12
0
Order By: Relevance
“…The increase in FW with T 1 was mainly due to higher availability of nutrients at T 1 throughout the growing season. These results are in accordance with the findings of Chatzitheodorou et al (2004) and Kabeel et al (2005). Moreover, some authors reported that the influence of organic fertilizers is not solely attributed to its content of nutrients but also to its beneficial effects on the soil structure and soil pH and used releasing fixed macro-and micronutrients (Eghaball and Power 1994).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The increase in FW with T 1 was mainly due to higher availability of nutrients at T 1 throughout the growing season. These results are in accordance with the findings of Chatzitheodorou et al (2004) and Kabeel et al (2005). Moreover, some authors reported that the influence of organic fertilizers is not solely attributed to its content of nutrients but also to its beneficial effects on the soil structure and soil pH and used releasing fixed macro-and micronutrients (Eghaball and Power 1994).…”
Section: Resultssupporting
confidence: 94%
“…In Harcot, the YE was higher in T 3 and lower in T 1 . It seems that response of apricots to fertilizers has an important genotype effect, as previously reported (Chatzitheodorou et al 2004). Interestingly, T 1 induced the lowest Y, CY and YE For T 1 -T 4 see section 'material and methods'; means followed by the same small letters, within the same column, are not significantly different (LSD at P ≤ 0.05) Vol.…”
Section: Resultssupporting
confidence: 73%
“…The increase of nutrients in the plants, especially N, can result in the formation of a greater number of flowers and vegetative buds on the shoots from the last vegetative cycle, which is reflected in an increase in yield components, such as fruit weight and diameter, and in the overall yield (Mattos, Freire, & Magnani, 1991). Chatzitheodorou, Sotiropoulos and Mouhtaridou (2004) also reported that the application of animal manure increased the peach yield in an orchard in Greece, which agrees with the results reported by Toselli, Baldi, Sorrenti, Quartieri and Marangoni (2010) and Baldi et al (2010a) in an orchard in Italy subjected to the application of organic compost. It is noteworthy that, especially in the 2008 crop season, the peach fruits from all treatments had diameters of between 5 and 6 cm and weighed between 80 and 100 g (Table 4).…”
Section: Nutritional Status and Fruit Yieldsupporting
confidence: 87%
“…The levels of organic compost did not affect the background color or length of the fruit soon after harvest and after 30 d of storage in a cold chamber during the 2008 and 2009 cropping seasons (Table 5). Chatzitheodorou et al (2004) also reported that the addition of animal manure to the soil in a peach orchard did not affect the fruit acidity. In addition, Crisosto, Johnson and Dejong (1997) indicated that the application of N sources in the soil did not affect the soluble solids values in the fruit.…”
Section: Peach Compositionmentioning
confidence: 95%
“…Xiahong et al (1998) and Rhee (1977) reported that nitrogen application during flower bud initiation in peach delayed the differentiation of pistil primordia. Working with 'Springtime' and 'Redhaven' peaches, Chatzitheodorou et al (2004) found that nitrogen, potassium and phosphorus applications reduced the percentage of the fruit with split and shattered pits. Beppu and Kataoka (1999) also speculated that double fruit formation may be related to hormones.…”
Section: Introductionmentioning
confidence: 99%